Oogenesis of Blackchin Tilapia, Sarotherodon melanotheron Rüppell, 1852 - พลาศัย อัมภรณ์พรรณ; เสนารัตน์ ศิลปชัย; เกษตระทัต เจษฏ์; จิรอังกูรสกุล วรรณีย์; โกสิยะจินดา พหล; เพ็งสกุล ธีรกมล; ภารา ชำนาญ (YRU Journal of Science and Technology, 2019)
The Blackchin Tilapia, Sarotherodon melanotheron, was introduced into Thailand from Africa Continent since 2006 to breed as a domestic fish. It has currently become an invasive species in Thailand. The state of its escape into natural water resource causes a damage to food chain in the ecological system of local aquatic fish in Thailand, especially in Mae Klong river, with the decreasing number of local aquatic animals. It becomes a widely discussed issue and leads to the question why it reduces rapidly. In this current study, we initially investigated the female germ cells in S. melanotheron starting from the background to the prediction of its egg quality using the histological technique. All specimens (n = 10) with a total length of more than 16 cm, which were generously donated from local fisheries during December 2017 to Febuary 2018. The results revealed that the gonadasomatic index (GSI) was 2.13±1.23 (Mean ± SD). The oogenesis of S. melanotheron can be distinguished into four stages as follows: (I) oogonial proliferation; (II) primary oocyte growth with composing of perinucleolar and oil droplets and cortical alveoli steps; (III) secondary, oocyte growth with consisting of early secondary growth, late secondary growth and full-grown oocyte steps; and (IV) atretic oocytes. The occurrence of the atretic oocyte was found only in the secondary oocyte growth in which the number of this feature accounted for 4 percent of the atretic oocyte. It indicated that the characterization of the egg in S. melanotheron was considered to be of high quality, which signified the strong link to a highly successful fish breeding.